Uji Daya Bunuh Umpan Blok Umbi Gadung (Dioscorea hispida L) terhadap Tikus - Ningtyas, Dyka Arya Ratna; Cahyati, Widya Hary (Universitas Ahmad Dahlan, 2017)
Background: Leptospirosis disease control relies on vector control is rodent animals. The use of natural rodenticides should be developed to reduce the negative impact of chemical rodenticides. Yam tuber contains alkaloids, including dioscorin and cyanide are toxic. This study was conducted to determine the effectiveness of the use of bait blocks yam tubers for mice. Method: This was experimental research, post test was conducted with control group design for 4 groups, namely the concentration of 30%, 50%, and 70% to the total sample examined was 28 mus musculus. Result: The test results showed that there was corelation between the feed block yam tubers with mortality of the mice (p= 0.001). The data was analyzed with univariate and bivariate. Probit analysis obtained bait blocks LC50 and LC90 was 34.024% is 59.298%. In LT50 and LT90 are 2.206E5 minutes 2.018E6 minutes. Conclusion: Conclusions from this research is a block yam tubers have the effect of rodenticides for mus musculus, but it can not effective as rodenticides. The researchers suggest there should be a further research on the active ingredients contained in yam tuber with just taking alkaloid content. Keywords: mus musculus, feed blocks, yam tubers.